A singular (p, q)-equation with convection and a locally defined perturbation. (August 2021) - Papageorgiou, Nikolaos S.; Vetro, Calogero; Vetro, Francesca
Abstract: We consider a parametric Dirichlet problem driven by the ( p, q ) -Laplacian and a reaction which is gradient dependent (convection) and the competing effects of two more terms, one a parametric singular term and a locally defined perturbation. We show that for all small values of the parameter the problem has a positive smooth solution.